Electron spin resonance: analysis and interpretation. - Rieger, Philip H; Rieger, Philip H (NBN International, 2007)
This book is an introductory level textbook which presents the fundamental concepts of the subject in a simple pedagogical manner. It therefore offers an ideal starting point for any student wishing to understand and analyze ESR spectra in solution and solid state. The book is concise and clearly written with the beginner in mind, since the extensive use of complex and difficult theory is kept to a minimum. It contains numerous illustrative and worked examples throughout, covering the fundamental core ideas in continuous wave ESR and also providing an excellent overview on the many applications of this technique. The book has a strong 'chemistry feel', reflecting the author's life-long interests in organometallic species, so at all times the theory and analyses are constantly related back to solving real chemical problems. Furthermore, the numerous subtle perturbations that determine the final appearance of an ESR spectrum are emphasized and explained, enabling the reader to approach an interpretation armed with the best possible advice and guidance.